1993
DOI: 10.4319/lo.1993.38.2.0299
|View full text |Cite
|
Sign up to set email alerts
|

Response of metallothionein concentrations in a freshwater bivalve (Anodonta grandis) along an environmental cadmium gradient

Abstract: Surficial (oxic) sediments, overlying water, and specimens of the freshwater bivalve Anodonta grandis were collected by divers at 11 littoral lacustrine sites located along a geochemical gradient of pH, [Cd], Dl, and [Z n in an area influenced by mining and smelting activities. The molluscs were dissected (gills; 1 hepatopancreas; remaining tissues) and analyzed for Cd, Cu, Zn, and metallothioneins (MT). Tissue concentrations of MT in A. grandis varied between 100 and 440 nmol metal binding sites (g dry wt-l. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
56
1
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 27 publications
7
56
1
3
Order By: Relevance
“…Lakes surrounding the industrial region of Rouyn-Noranda in northwestern Québec have been affected by mining and smelting operations since about 1927 (Couillard et al 1993). Although the extent of industrial contamination is considerably smaller in the Rouyn-Noranda region than in Sudbury, recent studies have demonstrated elevated concentrations of Cd, Cu, and Zn in contaminated lakes relative to background concentrations (Couillard et al 1993;Brodeur et al 1997;Laflamme et al 2000;Sherwood et al 2000;Levesque et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Lakes surrounding the industrial region of Rouyn-Noranda in northwestern Québec have been affected by mining and smelting operations since about 1927 (Couillard et al 1993). Although the extent of industrial contamination is considerably smaller in the Rouyn-Noranda region than in Sudbury, recent studies have demonstrated elevated concentrations of Cd, Cu, and Zn in contaminated lakes relative to background concentrations (Couillard et al 1993;Brodeur et al 1997;Laflamme et al 2000;Sherwood et al 2000;Levesque et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Les échantillons ont été conservés à -20 °C jusqu'au moment de l'analyse qui fut réalisée à l'automne. Les détails des procédures d'extraction et d'analyse en laboratoire sont donnés dans COUILLARD et al (1993).…”
Section: Récolte D'eau Et De Sédiments Pour L'analyse Des Métauxunclassified
“…Le surnageant était analysé pour la MT à l'aide d'une technique de saturation au mercure dont la méthode est décrite plus en détail dans COUILLARD et al (1993). Comme contrôle de qualité, le pourcentage de récupération d'un standard de MT (foie de lapin, Sigma Chemical Co.) a été déterminé à chaque essai analytique.…”
Section: Récolte Des Espèces Sentinelles Et Dosage Des Métaux Et De Lunclassified
“…Metals have contaminated many lakes in the area, and their effects on fish and invertebrates in the region have been regularly studied since the early 1990s [1][2][3][4]. Research has also demonstrated that the physiology of yellow perch (Perca flavescens) living in these contaminated systems is affected [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%